Iberoamerican tax moot court competition : applicant memorandum (tax payer) (2017)
"Today more than ever the challenges posed by international taxation are exacerbated to be the focus of the most professional experts in the field. It is not only because of the tensions inherent to taxation when it transcends the frontiers of sovereign States, but also because it is a fact that international organizations such as the Organization for Economic Cooperation and Development (OECD), are directly attacking evasion and the deliberate allocation of profits in jurisdictions of low or null taxation from the root. This document presents some of the problems regarding Double Taxation Conventions and, particularly, articles 17 and 7 of the OECD Model." -- Tomado del Formato de Documento de Grado.